Classification, principles, and determinants of the valuation of digital intellectual assets of the university (Economics and region, 2025)
The article explores the methodological aspects of the digital transformation of the economy and universities, focusing on how higher education adapts to digital technologies. Digitalization is identified as a key driver of economic, social, and educational development, opening opportunities for learning, research, and management. The study highlights the role of mobile platforms, interactive teaching, and electronic services in improving access to resources, fostering individualization of learning, and enhancing management efficiency. It emphasizes the need for strategic planning and institutional support to ensure sustainable development. The findings confirm that digitalization changes the structure of the educational process, improves quality, and strengthens university competitiveness in a globalized environment.
Keywords: digital intellectual assets; valuation; digitalization; digital university; digital transformation